L'immixtion et la trop grande expertise du propriétaire, cause d'exonération de responsabilité des architectes et des entrepreneurs sous l'article 1688 C.C. - Rivet, Michèle (Les Cahiers de droit, 1978)
In May 1977, the Supreme Court of Canada gave an authoritative judgment on the interpretation of article 1688 of the Civil Code dealing with the liability of the builder and the architect. In Davie Shipbuilding Ltd v. Cargill Grain Company Ltd and The Foundation Company of Canada Ltd, the court established a new method of rebutting the presumption of liability resulting from the article. Indeed, the Supreme Court found that where the owner intervened during the construction and was more qualified than the contractors in charge of the work to judge its quality, he could not invoke the presumption resulting from article 1688 C.C. and was responsible for any loss. The case is not an easy one — questions of law and facts are not simple in this dispute involving more than eleven million dollars.